Study on High-Speed Machining of 2219 Aluminum Utilizing Nanoparticle-Enhanced Minimum Quantity Lubrication (MQL) Technique - Sagil James; Mehrshad Mazaheri (Surfaces, 2023)
High-speed machining processes are significantly affected by the accumulation of heat generated by friction in the cutting zone, leading to reduced tool life and poor quality of the machined product. The use of cutting fluids helps to draw the heat out of the area, owing to their cooling and lubricating properties. However, conventional cutting fluid usage leads to considerable damage to human health and the environment, in addition to increasing overall manufacturing costs. In recent years, minimum quantity lubrication (MQL) has been used as an alternative lubricating strategy, as it significantly reduces cutting fluid consumption and eliminates coolant treatment/disposal needs, thereby reducing operational costs. In this study, we investigated microstructural surface finishing and heat generation during the high-speed cutting process of 2219 aluminum alloy using an MQL nanofluid. 2219 aluminum alloy offers an enhanced strength-to-weight ratio and high fracture toughness and is commonly used in a wide range of aerospace and other high-temperature applications. However, there is no relevant literature on MQL-based high-speed machining of these materials. In this study, we examined flood coolant and five different MQL nanofluids made by synthesizing 0.2% to 2% concentrations of Al2O3 nanoparticles into ultra-food-grade mineral oil. The study results reveal the chemistry between the MQL of choice and the corresponding surface finishing, showing that the MQL nanofluid with a 0.5% concentration of nanoparticles achieved the most optimal machining result. Furthermore, increasing the nanoparticle concentration does result in any further improvement in the machining result. We also found that adding a 0.5% concentration of nanoparticles to the coolant helped to reduce the temperature at the workpiece–tool interface, obtaining a good surface finish.